A Review of Ganoderma lucidum Polysaccharide: Preparations, Structures, Physicochemical Properties and Application - Yuanbo Zhong; Pingping Tan; Huanglong Lin; Di Zhang; Xianrui Chen; Jie Pang; Ruojun Mu (Foods, 2024)
Ganoderma lucidum (GL) is a kind of edible fungus with various functions and a precious medicinal material with a long history. Ganoderma lucidum polysaccharide (GLP) is one of the main bioactive substances in GL, with anti-tumor, anti-oxidation, anti-cancer, and other biological activities. GLP is closely related to human health, and the research on GLP is getting deeper. This paper reviewed the extraction and purification methods of GLP, the relationship between structure and activity, and the qualitative and quantitative methods. This review provides solutions for the analysis and application of GLP. At the same time, some new methods for extraction, purification and analysis of GLP, the relationship between advanced structures and activity, and future applications of and research into GLP were emphasized. As a kind of bioactive macromolecule, GLP has unique functional properties. Through the comprehensive summary of the extraction, purification, and analysis of GLP and its future prospects, we hope that this review can provide valuable reference for the further study of GLP.